Development of recombinant subunit vaccines against Flavobacterium covae and Flavobacterium columnare in grass carp (Ctenopharyngodon idellus): Evaluation of protective efficacy and antibody immune response - Zhongning He; Rui Han; Huicheng Wu; Xueming Dan; Yanwei Li; Zequan Mo (Aquaculture, 2027)

Integrated physiological and multi-omics analysis identifies MdMAPKKK17-mediated anthocyanin suppression in apple red-skin patterning - Chunyu Li; Yishu Xu; Yuchen Li; Meihua Mo; Xudong Guo; Xiaoya Han; Huimin Wang; Xinyuan Wang; Xiuqi Sui; Yongbing Yuan; Dongjie Jia (Postharvest Biology and Technology, 2026)

Pre-biodrying enhances compost humification via redirecting carbon allocation towards microbial necromass formation - Yujie Han; Yuzhou Long; Jiefei Mo; Chenxuan Fang; Liqing Xin; Yong Qin; Weixiang Wu (Bioresource Technology, 2026)

PoGPx-7, a glutathione peroxidase homolog from teleosts, exhibits bactericidal activity and activates host immune cells against bacterial infection - Xin-yi Jiang; Xue-pin Han; Jia-hang Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2026)

Energy absorption and structural optimization of plum multi-cell tubes with origami - Yue Zhou; Minsi Ji; Shuo Han; Zhuangzhuang Li; Zonglai Mo; Jun Li (Engineering Structures, 2026)

Antibacterial cellulose acetate-based nanofiltration membrane through silver-assisted interfacial polymerization for efficient low-pressure desalination - Jian Zhang; Lianghui Zhong; Dongyang Han; Minfu Mo; Hui Zhang; Liulian Huang; Dong Wang (Journal of Water Process Engineering, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Highly selective solar CO2 conversion into ethanol over metal-free sulfonated g-C3N4/nitrogen doped reduced graphene oxide hybrid photocatalyst - Sachin G. Ghugal; Amol U. Pawar; Park Kyoung Mo; Poonchi Sivasankaran Ramesh; Harish Reddy Inta; Sanjeev Gupta; Sung-hoon Oh; Muhammad Zaeem Azam Khan; Young Seok Son; Hyunchul Shin; Hongxian Han; Young Soo Kang (Chemical Engineering Journal, 2026)

A universal flexographic-thermal transfer printing synergistic strategy for high performance PEDOT: PSS electrochromic devices on absorbent substrates - Haixiang Hu; Lixin Mo; Ziyun Han; Mingtian Geng; Haoyou Zhang; Shaobo Han; Lantian Liu; Jingke Zhang; Zhiqing Xin; Kun Hu; Zihao Li (Chemical Engineering Journal, 2026)

AI-2 type quorum-sensing signal enhances mercury resistance and adsorption in thermotolerant Bacillus subtilis - Shuo Han; Qianyun Mo; Xiaobin Wen; Xiangru Wang; Xiangqian Wang; Yao Yu; Yixiao Yang; Chunzhe Yang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Feasibility-enhanced and cluster-guided optimization for coordinated hydro-wind-photovoltaic dispatch under cross-regional power delivery - Zixuan Liu; Yuliang Han; Songyan Hu; Wan Liu; Wenjing Xiao; Xutong Sun; Qin Shen; Li Mo (Journal of Cleaner Production, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Improving groundwater level prediction based on optimized deep learning model with Coati algorithm - Rana Muhammad Adnan; Jing-Cheng Han; Mo Wang; Sandeep Samantaray; Abinash Sahoo; Sajjad Firas Abdulameer; Mohammad Al-Suwaiyan; Zaher Mundher Yaseen (Environmental Modelling & Software, 2026)

Facile fabrication of high-performance hollow fiber-supported porous organic cage membranes via Zn2+-bridging for advanced helium separation - Tianliang Han; Qi Wu; Pengfei Xing; Hongying Mo; Baoru Yu; Zhenyuan Li; Can Wang; Lili Gong; Shuangjiang Luo (Chemical Engineering Journal, 2026)

Fucosylated human milk oligosaccharides: A comprehensive review from structure and function to biomanufacturing and industrial perspectives - Mengli Li; Jiawei Yao; Ruoyu Jia; Mo Han; Ming Miao; Tao Zhang (Carbohydrate Polymers, 2026)

Loss of ROC5 Induces Leaf Rolling with Pleiotropic Yield Penalties and Transcriptomic Shifts in Rice - Hyun-oh Lee; Sieun Choi; Yeeun Jun; Yurim Kim; Jiheon Han; Hwarim Kim; Minje Lee; Song Lim Kim; Sang-Ho Kang; Eun-Jung Suh; Seong-Woo Cho; Youngjun Mo (Journal of Plant Biology, 2026)

Coordinated nitrogen placement and rate optimization strengthen root–nitrogen coupling and improve nitrogen use efficiency in dryland maize - Fu Liu; Xiaoyu Ning; Jiaming Yang; Zijun Han; Yunfei Ren; Jinxia Wang; Haibo Hu; Yi Zhou; Xiaogang Yin; Shikun Sun; Juan Han; Yuncheng Liao; et al. (Soil and Tillage Research, 2026)

Retraction notice to “Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices” [Sci. Total Environ. 925 (2024) 171564] - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2026)

Synergistic depression of chalcopyrite by Fe(II) and Na2S in Chalcopyrite-Molybdenite separation: Mechanism investgation and industrial validation - Zhian Liang; Langfeng Tang; Zhenpeng Han; Tao Yue; Songtao Yang; Qiankun Wang; Zhenjun Mo; Haixiang Wu; Zhuanhua Wei; Yan Miao; Luzheng Chen (Minerals Engineering, 2026)

Integrated transporter engineering and metabolic flux redistribution for efficient production of 3-fucosyllactose in Escherichia coli - Ruoyu Jia; Mengli Li; Mo Han; Juan Zhang; Ming Miao; Tao Zhang (Food Bioscience, 2026)

Reservoir inflow forecasting using a large language model and time series approach - Zixin Song; Ping-an Zhong; Yiwen Wang; Yu Han; Bin Wang; Xinyuan Qian; Ran Mo; Weifeng Liu; Jing Liu (Environmental Modelling & Software, 2026)

A design framework for smart home energy management systems interfaces to promote energy-saving behaviors - Jinmog Han; Yunjeong Mo (Energy and Buildings, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

A Novel Cyclopentane Pyridine Compound Identified from Saccharothrix syringae NRRL B-16468 by PPTase-Based Activation - Yuxing Bi; Xu Han; Guihong Yu; Yueliang Yao; Song Yang; Xuhua Mo (Current Microbiology, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

Early development of stem units and the modular organization of the branch in Norway spruce - Carol L. Wenzel; Anson Mo; Bonita Chan; Anny Xia; Chantelle Westgate; Rebecca Saunders; Han Han Ly; David M. Holloway (Trees, 2026)

Exploratory observation of dietary exogenous bile acids on growth, hepatic glucose metabolism, intestinal and liver health, and fillet quality of Monopterus albus fed high-carbohydrate diets - Jiamin Li; Peng Fang; Ao Luo; Luyao Xu; Tianlun Luo; Junzhang Han; Tingting Li; Xiaoxuan Qi; Shuo Cheng; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2026)

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Single-cell and spatial transcriptomics identify PGK1-sensitized hypoxia macrophages as a therapeutic target to overcome PDT resistance in glioma - Xiuwei Yan; Jiahe Hu; Xuyan Han; Lei Xu; Lihui Zhou; Jiaoyan He; Fei Yang; Longgang Zhou; Yapeng Niu; Mo Geng; Wenjie Yuan; Dong Zhao; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Mariana trench-derived fungal polysaccharide AVP214–1 inhibits Singapore grouper iridovirus infection in vitro and in vivo - Xinyu Liao; Gaoqi Yu; Xiaohui Zheng; Yanqi Zhao; Siting Wu; Weifu Mo; Yijie Lin; Xiaoyong Zhang; Zhuang Han; Qiwei Qin; Jingguang Wei (Aquaculture, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Nocturnal water balance shifts: Uncovering the forces driving transpiration and refilling in a montane forest - Hongjuan Zhou; Lu Han; Kangle Mo; Guodong Jia; Lixin Chen; Zhiqiang Zhang (Agricultural and Forest Meteorology, 2026)

Catalytic property tuned ozone gas sensing performance of cobalt oxides - Qiuyi Zhu; Jian Guan; Linghao Wu; Ning Han; Jinhan Mo; Yunfa Chen (Journal of Environmental Sciences, 2026)

Reprogramming lipid metabolism and morphology engineering in Yarrowia lipolytica for algae-free, high-titer production of esterified astaxanthin - Mo-Han Zhu; Hong-Ze Zhou; Zhijie Liu; Hong Zhu; Jun Chen; Chen Yang; Feng Liu; Qiang Hua (Chemical Engineering Journal, 2026)

Development and Evaluation of Antioxidant Postbiotics from Bacillus amyloliquefaciens C-1 to Alleviate DSS-Induced Colitis - Xinyao Hou; Jiayu Feng; Jiale Qin; Jianhui Mo; Rong Yu; Jia Lv; Shaoru Li; Jing Tian; Yue Cheng; Bei Han (Probiotics and Antimicrobial Proteins, 2026)

From theory to practice: improving Lynch syndrome recognition through evidence-based education - Silvia Sanduleanu-Dascalescu; Gabriel Dimofte; Han-Mo Chiu; Bogdan Cotruta; Stefan Morarasu; Hans Vasen (Familial Cancer, 2026)

Modulation of the nanoscale chimney effect in metal–organic frameworks enables efficient guest diffusion and separation - Sha-Sha Meng; Hanxi Guan; Han Yang; Hai-Yue Wei; Mo-Han Gu; Jian Zhang; Ming Xu; Lina Wu; Zhi-Yuan Gu (Science Bulletin, 2026)

Tuning the upper porous structure to improve antibiotic removal performance of an electroactive membrane in the presence of realistic effluent organic matters - Yinghui Mo; Jinxue Han; Yihan Wang; Liang Wang; Lei Tian (Journal of Environmental Chemical Engineering, 2026)

Quantifying the impact of nanoplastics and natural particles on copper accumulation and distribution in zebrafish: Coupling in vivo tests with toxicokinetic modeling - Xiaorong Luo; Xue Yu; Chenglong Han; Ning Gao; Xunqiang Mo; Jianfeng Feng; Xueqiang Lu (Environmental Pollution, 2026)

A fully self-breathing, liquid metal-fed, solid oxide cell for high-density energy storage - Xin Gu; Yidong Jiang; Chaojun Liu; Peidong Song; Wenfei Mo; Qiaoxia Zhu; Yaowei Hao; Xiaoyi Liu; Meng Han; Yixiang Shi; Ningsheng Cai; Zongping Shao (Chemical Engineering Journal, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

Structural reconstruction-induced electronic Kagome lattices with low-energy flat bands in twisted double bilayer graphene - Mo-Han Zhang; Yalei Zhang; Chen-Yue Hao; Zi-Han Guo; Chao Yan; Ya-Xin Zhao; Ya-Ning Ren; Jin-Hua Gao; Shengjun Yuan; Lin He (Science Bulletin, 2026)

Hierarchically structured fiber scaffold incorporating functionalized microspheres for sustained drug release and treatment of infected wounds - Hao Feng; Gonghao Zhang; Sidong Zhang; Lu Han; Zhengchao Yuan; Xiao Yu; Shuqi Lou; Yunhan Ji; Muhammad Shafiq; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Xiumei Mo; et al. (Chemical Engineering Journal, 2026)

Sr2Sb2O7: A multifunctional oxide platform for cyan-compensated healthy lighting and near-infrared applications - Changle Luo; Yanbing Han; Qingqing Mo; Xiaoyang Xing; Shiyu Zhu; Han Gao; Jinghuo Chen; Zhuangzhuang Ma; Mochen Jia; Linyuan Lian; Jibin Zhang; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Addition of chemical oxidation catalysts accelerates heating and humification in biodrying-enhanced composting process for kitchen waste - Chenxuan Fang; Jiefei Mo; Yuzhou Long; Yujie Han; Yong Qin; Qingqing Mei; Weixiang Wu (Bioresource Technology, 2026)

Chromosomal variations and evolution in Arachis species revealed by single-copy FISH karyotyping - Guoquan Chen; Qian Wang; Haojie Sun; Liuyang Fu; Xiaobo Wang; Ziqiang Mo; Lijuan Miao; Suoyi Han; Hua Liu; Lina Li; Chenyu Li; Mingbo Zhao; et al. (Theoretical and Applied Genetics, 2026)

A top-down deep neural network for multi-dairy cows pose estimation and lameness detection - Saisai Wu; Shuqing Han; Xiaoxiang Mo; Yingying Wei; Yuanyuan Qin; He Chen; Jianzhai Wu; Zhikang Zeng (Computers and Electronics in Agriculture, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Unraveling strong and weak interaction mechanisms for the synergistic removal of divalent heavy metals and tetracycline by multifunctional magnetic biochar - Guanhai Mo; Fupeng Li; Jinnan Xiao; Zhengui Han; Zhenming Zhang (Chemical Engineering Journal, 2025)

GSDMD deficiency mitigates intestinal damage via macrophage pyroptosis control in experimental NEC - Yihang Yang; Xinyi Yang; Yue Ma; Xinli Liu; Dandan Mo; Cuilian Ye; Qin Deng; Wenli Han; Xionghui Ding; Chunbao Guo (Inflammation Research, 2025)

Characterisation and diagnostic model of monogenic lupus - Mengyang Yang; Dan Lu; Yulu Li; Xiongbin Chen; Han Yang; Wenxiu Mo; Huawei Mao (Immunologic Research, 2025)

TFAP2A-regulated CRNDE enhances colon cancer progression and chemoresistance via RIPK3 interaction - Xin Gao; Yanming Huang; Tonghui Wei; Jingmin Xue; Filippov Iurii; Laishou Yang; Liying Wang; Hao Li; Genshen Mo; Yuze Huang; Haonan Xie; Hang Wang; et al. (Functional & Integrative Genomics, 2025)

Concentration, speciation and origin of lead (Pb) in alluvial agricultural soils in the world’s largest continuous karst terrain, southwestern China - Zhixuan Han; Yifan Liu; Yuhong Mo; Ruiwei Zhao; Yuqun Cai; Shen Huang; Xiaolong Lin (Environmental Geochemistry and Health, 2025)

Multi-criteria carbon emission allowance allocation for liner shipping companies in China: An integrated approach based on composite indicators and zero-sum gains DEA - Mo Zhu; Yuquan Du; Mei Sha; Yiwen Jiang; Zhongdai Wu; Bing Han (Ocean & Coastal Management, 2025)

Origin of granitic pegmatites: Perspectives from elements and Li Hf isotopes, Chakabeishan, northern Tibetan Plateau - Wenli Sun; Zhidan Zhao; Xuanxue Mo; Guochen Dong; Xiaowei Li; Wanming Yuan; Tao Wang; Bingzhang Wang; Tong Pan; Jie Han; Yan Tang; Ningyuan Qi; et al. (Lithos, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Study on the characteristics of vibration acoustic signals and rupture grading for reactor pipeline leaks - Xinyu Zhao; Zhuorun Zhang; Xiangpeng Du; Yu Wang; Jinchuan Yang; Zhangjun Feng; Ruiyang Zhong; Chuang Han; Jiaxin Mo; Jinlong Wan; Zhida Yang (Annals of Nuclear Energy, 2025)

Environmental impacts of concentrated apple juice supply chain based on the major apple producing regions in China - Zhiyao Chang; Wenxue Li; Minghao Zhuang; Mingzhao Han; Yu Peng; Mo Li; Yuanying Ni; Xin Wen (Science of The Total Environment, 2025)

Characterization of rainwater infiltration within a controlled experiment by self-potential monitoring and modeling - Kaiyan Hu; Qinghua Huang; Peng Han; Yihua Zhang; Chunyu Mo; Shuangshuang Li; Damien Jougnot (Journal of Hydrology, 2025)

Integrating genotype-by-environment interaction and machine learning to evaluate yield-related traits in Korean rice cultivars - Seung Young Lee; Hayeong Lee; Jiheon Han; Ji-Ung Jeung; Youngjun Mo (Journal of Crop Science and Biotechnology, 2025)

Combined effects of tree canopy and root systems on soil hydraulic properties: A field monitoring of a Populus alba - Xu-Guang Gao; Ji-Peng Wang; Xian-Wei Li; Shangqi Ge; Huan-Xiang Qiu; Mo-Han Bai (Rhizosphere, 2025)

The roles of effluent organic matters, inorganic ions, and their interplay in affecting antibiotic degradation by an electroactive membrane - Yinghui Mo; Yihan Wang; Liang Wang; Jinxue Han; Lei Tian (Journal of Hazardous Materials, 2025)

Catalytic fast pyrolysis of waste battery separators with limited removal of the Al2O3 layer for selective aromatic hydrocarbons production over HZSM-5 catalyst - Li Zhao; Wan-zhao Huang; Shi-guan Yang; Qi Niu; Shi-yu Feng; Pu-cheng Wang; Ying Mo; Yu-han Fan; Kai Li; Qiang Lu (Journal of Environmental Management, 2025)

A review and perspective of magnetic-controlled microbots for medical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Jiufei Luo; Mengjie Shou; Xinglong Gong; Zhihao Zhou (Chemical Engineering Journal, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Pre-biodrying enhanced lignin degradation to promote aromatic macromolecular humic acid formation in double-phase composting - Jiefei Mo; Changxun Zhao; Chenxuan Fang; Yuzhou Long; Yujie Han; Qingqing Mei; Weixiang Wu (Waste Management, 2025)

Impact of ARTP mutagenesis on the selection of salt-tolerant, aroma-producing yeasts and their contribution to the flavor of fermented soy sauce - Zhanyu Shen; Fanghua Mo; Lei Wang; Yu Su; Huijing Han; Kaiyue Zheng; Chunling Wang (Food Bioscience, 2025)

Characterization and functional analysis of the small heat shock protein HSP19.5 in Bombyx mori in response to Nosema bombycis infection - Zhenghao Han; Shidong Jiang; Jingxian Xie; Ibouanga Sama Lucreche Poupina; Xiaoli Mo; Li Sui; Ping Qian; Xudong Tang (Journal of Invertebrate Pathology, 2025)

Quality decline of prepared dishes stored at 4 °C: Microbial regulation of nitrite and biogenic amine formation - Jiaxin Liu; Yin Wang; Ping Yang; Hongbo Li; Haizhen Mo; Prince Chisoro; Dong Han; Chunhui Zhang (Food Microbiology, 2025)

Localized and systemic abilities of arbuscular mycorrhizal fungi to control growth, antioxidant defenses, and the nutrient uptake of alfalfa under uniform and non-uniform salt stress - Xue Xiong; Yu-qi Wei; Mo-han Liu; Nan Liu; Ying-jun Zhang (Plant and Soil, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Magnetic field-assisted bioleaching of cathode materials from spent Li-ion batteries using Acidithiobacillus ferrooxidans - Jun-Ho Hong; Jeon Kim; Ejin Han; Seon-Mo Yang; Hee-Soo Kim; Jihwan Kim; Chong Seung Yoon (Chemosphere, 2025)

2-Dodecyl-6-Methoxycyclohexa-2,5-Diene-1,4-Dione from Averrhoa carambola L. roots: Suppressing hepatocellular carcinoma progression through ROS accumulation and p53 pathway-mediated apoptosis - Meifeng Chen; Hongbing Pang; Thi Thai Hoa Pham; Yongfei He; Qiang Gao; Yuan Liao; Chunyi Zhu; Linqian Chen; Guohong Yan; Shutian Mo; Chuangye Han (Toxicology and Applied Pharmacology, 2025)

Effects of polylactic acid microplastics on dissolved organic matter across soil types: Insights into molecular composition - Liying Chen; Hongkai Huang; Lanfang Han; Liang Chao; Xuanwei Zhang; Beibei Liu; Chenyan Luo; Weiling Mo; Yanpeng Cai; Zhifeng Yang (Journal of Hazardous Materials, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Advanced partially holey reduced graphene oxide inks for 3D printing self-healing thick electrodes with ultra-high areal desalination capacity - Rui Wang; Biao Fang; Han Liang; Runwei Mo (Desalination, 2025)

Functional analysis of the woody oil crop Plukenetia volubilis L. LEC2 homolog PvoB3-69 in promoting regeneration - Jing-jing Yu; Shiling Deng; Jinhui Mo; Han Huang; Zeng-Fu Xu; Yi Wang (Plant Cell Reports, 2025)

Predicting the adsorption capacity of geopolymers for heavy metals in solution based on machine learning - Yongming Han; Wenting Dai; Lu Zhou; Lisheng Guo; Mo Liu; Dehong Wang; Yanzhong Ju (Journal of Environmental Chemical Engineering, 2025)

Lactiplantibacillus plantarum T34 alleviates constipation by enhancing intestinal barrier and modulating gut homeostasis - Fei Shen; Huiting Zhu; Zhongyan Bao; Di Han; Juan Du; Minjie Zhao; Fengqin Feng; Guanghua He; Qiufen Mo (Food Bioscience, 2025)

Identification of QTL for rice panicle length and grain weight using a doubled haploid population derived from 93–11 and Milyang352 - Jiheon Han; Seung Young Lee; Yeeun Jun; So-Myeong Lee; Gyu-Hyeon Eom; Jong-Hee Lee; Youngjun Mo (Plant Biotechnology Reports, 2025)

Allograft valves harvesting and preservation technique for enhanced performance - Congrui Wang; Xiumeng Hua; Qiuju Li; Shun Liu; Hao Jia; Hao Cui; Ningning Zhang; Zeyu Cui; Yuan Chang; Mengni Bao; Han Mo; Zhe Sun; et al. (Cell and Tissue Banking, 2025)

Biochar strategy for long-term N2O emission reduction: Insights into soil physical structure and microbial interaction - Yeye Zhang; Chun Yan; Tao Wang; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Soil Biology and Biochemistry, 2025)

Multi-level metabolic engineering of 6ʹ-sialyllactose in Escherichia coli - Chenchen Li; Mengli Li; Mo Han; Ming Miao; Tao Zhang (Food Bioscience, 2025)

Plasticization of gelatin/chitosan films with deep eutectic solvents and addition of Flos Sophora Immaturus extracts for high antioxidant and antimicrobial - Quanling Zhao; Xi Huang; Lijun Qian; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

ComDMFT v.2.0: Fully self-consistent ab initio GW+EDMFT for the electronic structure of correlated quantum materials - Byungkyun Kang; Patrick Semon; Corey Melnick; Mancheon Han; Seongjun Mo; Hoonkyung Lee; Gabriel Kotliar; Sangkook Choi (Computer Physics Communications, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Identification and pharmacological characterization of pH-sensitive chloride channels in the fall armyworm, Spodoptera frugiperda - Wei Wang; Jia-Sheng Chen; Pei-Yun He; Mo-Han Zhang; Hai-Qun Cao; Subba Reddy Palli; Cheng-Wang Sheng (Insect Biochemistry and Molecular Biology, 2025)

Promoting the catalytic performance by tungstophosphoric acid modification Fe0.15Ce0.85 bimetal oxide catalysts for NH3-SCR - Chengheng Huang; Shifei Gu; Qiuju Qin; Xiaorong Han; Donghai Mo; Zhengjun Chen; Bin Li; Hongyan Zhang; Lihui Dong (Fuel, 2025)

Electron-proton hybrid conductor of H MoO3 for sweat pH monitoring - Yitian Tang; Sanyang Du; Yihan Wang; Xiaocheng Mo; Lijie Zhong; Yu Bao; Yingming Ma; Wei Wang; Dongxue Han; Shiyu Gan; Li Niu (Chemical Engineering Journal, 2025)

Electrospun 1D Al-LLZO incorporated PVDF-HFP composite electrolyte with fast Li+ pathway derived from highway-traction effect for high performance lithium metal batteries - Joo-Young Han; Sunghoon Kim; Dae Ung Park; Dongwoo Kang; Ji-Hui Oh; Da-Eun Hyun; Dong-Won Lee; Hwiyun Im; Jong-Min Oh; Sang-Mo Koo; Jeonghyun Kim; Jong Ho Won; et al. (Chemical Engineering Journal, 2025)

Advancements in programmed cell death research in antitumor therapy: a comprehensive overview - Shuxin Wei; Chuangye Han; Shutian Mo; Hailian Huang; Xiaoling Luo (Apoptosis, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Combined application of organic and inorganic fertilizers sustained rice yields and N accumulation and decreased soil-canopy system NH3 emission - Bo Shang; Tongtong Tian; Yatong Mo; Han Zhang; Kun Zhang; Evgenios Agathokleous; Yang Ji; Zhaozhong Feng (Agriculture, Ecosystems & Environment, 2025)

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Self-correcting deep learning for estimating rice leaf nitrogen concentration with mobile phone images - Jinmin Li; Liangsheng Shi; Xiaohu Mo; Xiaolong Hu; Chenye Su; Jingye Han; Xianzhi Deng; Shuai Du; Shenji Li (Computers and Electronics in Agriculture, 2024)

Oscillatory responses of a spatially random seabed in the vicinity of structures: Validation and application of the integrated CFD-SFEM - Bin Zhu; Yuan Sun; Tao Wang; Pinqiang Mo; Yunrui Han; Yubin Ren; Jiabo Li (Ocean Engineering, 2024)

Optimizing ABA-based chemically induced proximity for enhanced intracellular transcriptional activation and modification response to ABA - Zeng Zhou; Yue-Qi Wang; Xu-Nan Zheng; Xiao-Hong Zhang; Lu-Yao Ji; Jun-You Han; Ze-Cheng Zuo; Wei-Liang Mo; Li Zhang (Science China Life Sciences, 2024)

Streptomyces cathayae sp. nov., an endophytic actinobacterium from the root tissue of Cathaya argyrophylla - Ping Mo; Can Wu; Ruonan Han; Zhongyuan Chen; Yushuang Luo; Peng Xie; Li Li; Yun Wang (Antonie van Leeuwenhoek, 2024)

Towards equitable infrastructure asset management: Scour maintenance strategy for aging bridge systems in flood-prone zones using deep reinforcement learning - Amir Taherkhani; Weiwei Mo; Erin Bell; Fei Han (Sustainable Cities and Society, 2024)

Microbial life-history strategies and particulate organic carbon mediate formation of microbial necromass carbon and stabilization in response to biochar addition - Yeye Zhang; Tao Wang; Chun Yan; Yuze Li; Fei Mo; Juan Han (Science of The Total Environment, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Parabens, bisphenols, and triclosan in coral polyps, algae, and sediments from sanya, China: Occurrence, profiles, and environmental implications - Yiming Ge; Han Zhang; Jinfeng Fu; Zhihui Guo; Qiulu Dong; Jiaxin Yu; Zhiling Mo; Yuxi Lai; Jialei Yang; Shaoyou Lu (Environmental Pollution, 2024)

Research on the coordinate regulation behavior of window opening and split air conditioners usage during summer in mixed-cooling houses in hot-humid regions - Jie Han; Zhuoying He; Zhishan Li; Nan Mo; Fuhao Xie; Wei Yang; Chen Zhang (Energy and Buildings, 2024)

Photocurrent-polarity-switching photoelectrochemical and electrochemical dual-mode sensing platform for the highly selective detection of trenbolone - Feng Jiang; Shanghua Liu; Mengxiao Mo; Xinyu Liu; Dongyu Han; Qing Liu; Yueyuan Li; Yueyun Li; Yaqi Li; Qin Wei (Chemical Engineering Journal, 2024)

25-Hydroxycholesterol induces oxidative stress, leading to apoptosis and ferroptosis in extravillous trophoblasts - Ki Mo Lee; Tae Hoon Kim; Eui-Jeong Noh; Jae Won Han; Jong-Seok Kim; Sung Ki Lee (Chemico-Biological Interactions, 2024)

Investigation of canopy interception characteristics in slope protection grasses: A laboratory experiment - Xu-Guang Gao; Ji-Peng Wang; Shangqi Ge; Shuai-Kang Su; Mo-Han Bai; Bertrand Francois (Science of The Total Environment, 2024)

Passivating perovskite surface defects via bidentate chelation for high-performing solar cells - Mengting Han; Li’e Mo; Zhiqian Yang; Aiqing Sun; Hong Zhang; Bolin Li; Zhaoqian Li; Xianxi Zhang; Rahim Ghadari; Yang Huang; Linhua Hu (Chemical Engineering Journal, 2024)

Upcycling of Pb from lead smelting residues to lead halide perovskite for piezocatalytic hydrogen production - Xiaofeng Mo; Mengye Wang; Han Song; Jie Li; Zhen Wu; Zhang Lin (Chemical Engineering Journal, 2024)

Bovine serum albumin-based hydrogels: Preparation, properties and biological applications - Changxin Shi; Shubin Li; Chao Li; Hanyu Liu; Zhanyue Wang; Yihang Li; Mo Li; Xiangxiang Zhang; Wei Mu; Xiaojun Han (Chemical Engineering Journal, 2024)

Fabrication of carbon-coated iron-based porous heterogeneous Fenton catalyst and enhanced degradation performance towards ciprofloxacin - Yufan Mo; Chunxia Che; Wei Han; Feiran Chen; Jun Guan; Feng Zhang; Bo Yang; Xiangdong Ren; Huiyu Li; Saeed Ahmed; Yongjun Feng (Chemical Engineering Journal, 2024)

Allelopathy research on the continuous cropping problem of poplar (populus) - Tao Song; Jia-Xu Chen; Lin-Miao Shan; Yu-Chen Qian; Mo-Xian Chen; Jian-Gang Han; Fu-Yuan Zhu (Phytochemistry Reviews, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Effect of vegetation on unsaturated soil hydraulic and the slope stability under rainfall - Ji-Peng Wang; Mo-Han Bai; Yi-Ran Tan; Shangqi Ge; Xu-Guang Gao; Abdelali Dadda; Jing-Yi Shen; Jiong Zhang (Rhizosphere, 2024)

Autonomous self-healing strategy for flexible fiber lithium-ion battery with ultra-high mechanical properties and volumetric energy densities - Chenpeng Zhao; Rui Wang; Han Liang; Biao Fang; Ruqing Li; Ruilin Wu; Runwei Mo (Chemical Engineering Journal, 2024)

In-situ constructing ultrafine NiCo alloy confined in LDH nanoflower for efficient selective hydrogenation of furfural - Huiling Zhang; Jingnan Yang; Teng Zhao; Fujun Lan; Yixin Luo; Fei Han; Xianliang Qiao; Qingxin Guan; Mo Qiu; Wei Li (Chemical Engineering Journal, 2024)

Highly sensitive formaldehyde gas sensor based on SnO2/Zn2SnO4 hybrid structures - Guijun Fan; Jian Guan; Hang Yu; Qiuyi Zhu; Ning Han; Jinhan Mo; Yunfa Chen (Building and Environment, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

MicroRNA 429 regulates MMPs expression by modulating TIMP2 expression in colon cancer cells and inflammatory colitis - Seol-Hee Han; Ji-Su Mo; Ki-Jung Yun; Soo-Cheon Chae (Genes & Genomics, 2024)

Towards sustainable path: Measuring the effectiveness of natural resource utilization, renewable energy resources, fintech, environmental investments, and research & development - Yulin Wang; Mo Han; Kai Liu (Resources Policy, 2024)

Structure engineering and heteroatom doping-enabled high-energy and fast-charging dual-ion batteries - Chenpeng Zhao; Biao Fang; Rui Wang; Han Liang; Runwei Mo (Chemical Engineering Journal, 2024)

Needle and bud scale development in Picea abies - Carol L. Wenzel; Anny Y. Xia; Rebecca Saunders; Han Han Ly; Anson Mo; David M. Holloway (Trees, 2024)

Inhibitory effect of malonic acid on Microcystis aeruginosa: Cell morphology, oxidative stress and gene expression - Chunyang Tao; Xiaojun Niu; Dongqing Zhang; Yuejin Liu; Lingling Zhou; Yunhao Han; Yujing Mo; Kaixin Wu; Yu Lin; Zhang Lin (Algal Research, 2024)

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

RETRACTED: Spatio-temporal microbial regulation of aggregate-associated priming effects under contrasting tillage practices - Yeye Zhang; Yunfei Ren; Shenglin Zhou; Xiaoyu Ning; Xiukang Wang; Yanming Yang; Shikun Sun; Nangia Vinay; Michael Bahn; Juan Han; Yang Liu; Youcai Xiong; et al. (Science of The Total Environment, 2024)

Study on window-opening behavior of suburban sustainable life-pattern in residential buildings at Donglu town of Hezhou, China - Jie Han; Nan Mo; Jingyi Cai; Xinyue Li; Fuhao Xie; You Peng; Tao Feng (Journal of Cleaner Production, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Improving Sedum plumbizincicola genetic transformation with the SpGRF4–SpGIF1 gene and the self-excision CRE/LoxP system - Yixin Zhang; Yanlan Mo; Hongxu Ren; Xiaotong Wu; Liyuan Han; Zhenyuan Sun; Wenzhong Xu (Planta, 2024)

Correction to: Efects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Effects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Preconcentrating sensor systems toward indoor low-concentration VOC detection by goal-oriented, sequential, inverse design strategy - Yan Wang; Zhuo Chen; Qiwei Chen; Enze Tian; Ning Han; Jinhan Mo (Building and Environment, 2024)

Memristor-coupled dual-neuron mapping model: initials-induced coexisting firing patterns and synchronization activities - Bocheng Bao; Jingting Hu; Han Bao; Quan Xu; Mo Chen (Cognitive Neurodynamics, 2024)

Mineral evolution and catalytic mechanism in catalytic gasification of petroleum coke with coal/biomass ash - Xin Yu; Dunxi Yu; Congming Yu; Mo Cai; Jingkun Han; Ying Liu; Fangqi Liu; Minghou Xu (Fuel, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Effects of ridge tillage and peanut growth on the surface–subsurface runoff generation and soil loss in the red soil sloping farmland of southern China - Kenan Deng; Zhao Liu; Xudong Han; Yan Zhu; Guanfang Sun; Minghao Mo (Journal of Soils and Sediments, 2024)

A Heterozygous Phospholamban Variant (p.R14del) Leads to Left Ventricular Involvement and Heart Failure Phenotypes in Arrhythmogenic Right Ventricular Cardiomyopathy - Han Mo; Xiumeng Hua; Mengni Bao; Zhe Sun; Xiao Chen; Mengda Xu; Jiangping Song (Phenomics, 2024)

Active disturbance rejection control strategy for PEMFC oxygen excess ratio based on adaptive internal state estimation using unscented Kalman filter - Hongwei Yue; Hongwen He; Mo Han; Sikai Gong (Fuel, 2024)

Seasonal analysis of land surface temperature using local climate zones in peak forest basin topography: A case study of Guilin - Nan Mo; Jie Han; Yingde Yin; Yelin Zhang (Building and Environment, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

A mixed electronic-ionic conductor-based bifunctional sensing layer beyond ionophores for sweat electrolyte monitoring - Yitian Tang; Lijie Zhong; Yirong Zhang; Xiaocheng Mo; Yu Bao; Yingming Ma; Wei Wang; Dongxue Han; Shiyu Gan; Li Niu (Science Bulletin, 2023)

Preparation of curcumin-chitosan composite film with high antioxidant and antibacterial capacity: Improving the solubility of curcumin by encapsulation of biopolymers - Han Li; Yanling Jiang; Jisheng Yang; Rui Pang; Yanan Chen; Liuting Mo; Qiong Jiang; Zhiyong Qin (Food Hydrocolloids, 2023)

Flame behavior and temperature distribution of coupled fire induced by the interaction of hydrogen jet flame and pool flame - Liang Gong; Tianyu Mo; Xianwen Zheng; Yifei Han; Haoyu Wang; Xufeng Yang; Yuchun Zhang (Process Safety and Environmental Protection, 2023)

Piperlongumine induces apoptosis and autophagy via the PI3K/Akt/mTOR pathway in KB human cervical cancer cells - Eun-Ji Han; Eun-Young Choi; Su-Ji Jeon; Sang-Woo Lee; Jun-Mo Moon; Soo-Hyun Jung; Bumseok Kim; Sung-Dae Cho; Jeong-Seok Nam; Changsun Choi; Jeong-Hwan Che; Ji-Youn Jung (Food and Chemical Toxicology, 2023)

Tough, multifunctional, and green double-network binary solvent eutectogel with in-situ generation of lignin nanoparticles based on one-step dual phase separations for wearable flexible strain sensors - Jisheng Yang; Yawen Feng; Bingzhen Wang; Jianshuo Miao; Shihai Wei; Han Li; Liuting Mo; Zhiyong Qin (Chemical Engineering Journal, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Comprehensive analysis of a novel power and methanol coproduction process using landfill gas reforming and renewable hydrogen generation by an alkaline electrolyzer - Haitao Lin; Mo Han Zhang; Bhupendra Singh Chauhan; Awatif M.A. Elsiddieg; Mohamed Abdelghany Elkotb; Peng Zhu; Ruicheng Tian; Mohamed Abouelela (Journal of Cleaner Production, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Long-term probabilistic streamflow forecast model with “inputs–structure–parameters” hierarchical optimization framework - Ran Mo; Bin Xu; Ping-an Zhong; Yuanheng Dong; Han Wang; Hao Yue; Jian Zhu; Huili Wang; Guoqing Wang; Jianyun Zhang (Journal of Hydrology, 2023)

Characterization of modified rice straw biochar in immobilizing Bacillus subtilis 168 and evaluation on its role as a novel agent for zearalenone-removal delivery - Jie Han; Jiao Zhang; Jun Meng; Yuanqi Cai; Mo Cheng; Siyu Wu; Zeming Li (Journal of Hazardous Materials, 2023)

Evading the permeance-selectivity trade-off dilemma in electrospray-assisted interfacial polymerization polyamide thin-film composite membrane through electrospinning nanofibers interlayer - Jia-Hao Liu; Fei Xie; Han-Zhuo Ding; Jia-Wei Mo; Xiao-Gang Jin; Xiao-Hua Ma; Zhen-Liang Xu (Desalination, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Inactivation of epithelial sodium ion channel molecules serves as effective diagnostic biomarkers in clear cell renal cell carcinoma - Qian Zheng; Yifang Wang; Ran Zhao; Peipei Han; Jun Zhao; Limei Li; Xiaohui Zhou; Ping Li; Yingxi Mo; Xinli Pan; Wenqi Luo; Xiaoying Zhou (Genes & Genomics, 2023)

Ocean ambient noise on the Chukchi Plateau and its environmental correlates - Xuejing Mo; Hongtao Wen; Yanming Yang; Hongtao Zhou; Jingwei Yin; Xiao Han; Hongxia Chen; Hailin Ruan (Marine Environmental Research, 2023)

Effect of distance of vertical barrier wall to the release nozzle on the hydrogen concentration profile induced by impingement of unignited release of cryogenic hydrogen - Liang Gong; Yifei Han; Xianwen Zheng; Tianyu Mo; Haoyu Wang; Yongzheng Yao; Yuchun Zhang (Fuel, 2023)

A review on directional muscle cell growth in scaffolding biomaterials with aligned porous structures for cultivated meat production - Kummara Madhusudana Rao; Soon Mo Choi; Sung Soo Han (Food Research International, 2023)

Occurrence, risk, and treatment of ciprofloxacin and clarithromycin in drainage - Meng Li; Dengyu Ji; Malvin Subroto Pamudji; Ka Hei Lui; Yayi Zhao; Gaoshen Zhao; Shao-Qi Zhou; Ce-Hui Mo; Wei Han; King Lun Yeung (Chemical Engineering Journal, 2023)

Triclosan toxicity in a model cyanobacterium (Anabaena flos-aquae): Growth, photosynthesis and transcriptomic response - Jiezhang Mo; Linrong Han; Runnan Lv; Michael W.L. Chiang; Rong Fan; Jiahua Guo (Journal of Environmental Sciences, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Deciphering Functional Connectivity Differences Between Motor Imagery and Execution of Target-Oriented Grasping - Eunkyung Kim; Woo Hyung Lee; Han Gil Seo; Hyung Seok Nam; Yoon Jae Kim; Min-Gu Kang; Moon Suk Bang; Sungwan Kim; Byung-Mo Oh (Brain Topography, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Measurement and control of containing-fluorine particulate matter emission during spent pot lining combustion detoxification process - Funian Han; Liang Yu; Xinyun Mo; Lu Zhang; Jiaqi Jia; Jingmeng Dong; Shaopeng Gu (Journal of Hazardous Materials, 2023)

Ultrasensitive fluorescence detection of multiple DNA methyltransferases based on DNA walkers and hyperbranched rolling circle amplification - Siqi Zhang; Huahao Shao; Kai-Bin Li; Wei Shi; Yichao Wang; De-Man Han; Jinggang Mo (Analytica Chimica Acta, 2023)

The evaluation of N/P fate using the SPARROW model: a case study in an arid and semi-arid region, northern China - Haitao Chen; Jincheng Yin; Menglai Song; Han Ding; Fan Mo; Qiuru Ren; Guoguang Li; Shuang Song; Yuqiu Wang (Environmental Science and Pollution Research, 2023)

An interactive multi-criteria decision-making method for building performance design - Zhen Han; Xiaoqian Li; Jiaqi Sun; Mo Wang; Gang Liu (Energy and Buildings, 2023)

Soil tillage rather than crop rotation determines assembly of the wheat rhizobacterial communities - Tong Li; Huanxin Xie; Zhangheng Ren; Yuting Hou; Deqiang Zhao; Weiyan Wang; Ziting Wang; Yang Liu; Xiaoxia Wen; Juan Han; Fei Mo; Yuncheng Liao (Soil and Tillage Research, 2023)

Divergent responses in the gut microbiome and liver metabolome to ammonia stress in three freshwater turtles - Qin-Yuan Meng; Dong-Mei Mo; Han Li; Wan-Ling Wang; Hong-Liang Lu (Science of The Total Environment, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Effects of Fe(II)-activated persulfate/sodium percarbonate (PS/SPC) pretreatment on ultrafiltration membrane fouling control and mechanisms - Jiachen Mo; Tao Lin; Xue Zhang; Fuchun Jiang; Han Chen (Desalination, 2023)

Microbial contribution to organic carbon accumulation in volcanic ash soils - Hye In Yang; Nuri Baek; Jin-Hyeob Kwak; Sang-Sun Lim; Young-Han Lee; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2023)

Co-exposure to phenols and phthalates during pregnancy with the difference of body size in twins at one month old - Hong Mei; Langjing Deng; Jinying Xie; Xiaojie Li; Nanxin Wu; Liqin Hu; Guangtong Huang; Fanyu Mo; Da Chen; Han Xiao; Pan Yang (Chemosphere, 2023)

Estimation of Snow Cover over Mountain Region based on the Surface Wet-bulb Temperature Measurements - Ji-Han Sim; Baek-Min Kim; Jai-Ho Oh; Mo-Rang Huh; Namkyu Noh; Kwang-Hee Han (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Global pattern of soil priming effect intensity and its environmental drivers - Fei Mo; Chengjie Ren; Kailiang Yu; Zhenghu Zhou; Richard P. Phillips; Zhongkui Luo; Yeye Zhang; Yuteng Dang; Juan Han; Jian‐Sheng Ye; Nangia Vinay; Yuncheng Liao; et al. (Ecology, 2022)
The microbial priming effect—the decomposition of soil organic carbon (SOC) induced by plant inputs—has long been considered an important driver of SOC dynamics, yet we have limited understanding about the direction, intensity, and drivers of priming across ecosystem types and biomes. This gap hinders our ability to predict how shifts in litter inputs under global change can affect climate feedbacks. Here, we synthesized 18,919 observations of CO 2 effluxes in 802 soils across the globe to test the relative effects (i.e., log response ratio [RR]) of litter additions on native SOC decomposition and identified the dominant environmental drivers in natural ecosystems and agricultural lands. Globally, litter additions enhanced native SOC decomposition (RR = 0.35, 95% CI: 0.32–0.38), with greater priming effects occurring with decreasing latitude and more in agricultural soils (RR = 0.43) than in uncultivated soils (RR = 0.28). In natural ecosystems, soil pH and microbial community composition (e.g., bacteria: fungi ratio) were the best predictors of priming, with greater effects occurring in acidic, bacteria‐dominated sandy soils. In contrast, the substrate properties of plant litter and soils were the most important drivers of priming in agricultural systems since soils with high C:N ratios and those receiving large inputs of low‐quality litter had the highest priming effects. Collectively, our results suggest that, though different factors may control priming effects, the ubiquitous nature of priming means that alterations of litter quality and quantity owing to global changes will likely have consequences for global C cycling and climate forcing.

Geochemistry and zircon U-Pb-Hf isotopes of igneous rocks associated with the Dongnam Fe-Mo skarn deposit, Taebaeksan Basin, South Korea - Il-Hwan Oh; Sang-Mo Koh; Chul-Ho Heo; Bum Han Lee; Jieun Seo; Sang-Gun No; Seong-Jun Cho; Bong Chul Yoo (Geosciences Journal, 2022)

The contribution of nirK gene-containing thaumarchaea to denitrification and N2O production across coastal sediment and terrestrial ecosystems - Bing Han; Si-Yi Liu; Li-Li Han; Xiao-Tong Song; Liu-Ying Mo; Li-Mei Zhang (Journal of Soils and Sediments, 2022)

The global biogeography of soil priming effect intensity - Chengjie Ren; Fei Mo; Zhenghu Zhou; Felipe Bastida; Manuel Delgado‐Baquerizo; Jieying Wang; Xinyi Zhang; Yiqi Luo; Timothy J. Griffis; Xinhui Han; Gehong Wei; Jun Wang; et al. (Global Ecology and Biogeography, 2022)
Aim Fresh carbon (C) inputs to the soil can have important consequences for the decomposition rates of soil organic matter (priming effect), thereby impacting the delicate global C balance at the soil–atmosphere interface. Yet, the environmental factors that control soil priming effect intensity remain poorly understood at a global scale. Location Global. Time period 1980–2020. Major taxa studied Soil priming effect intensity. Methods We conducted a global dataset of CO 2 effluxes in 711 pairwise soils with 13 C or 14 C simple C sources inputs and without C inputs from incubation experiments in which isotope‐labelled C was used to quantify fresh C‐induced rather than exudate‐induced priming. Results Soil priming effect intensity is predominantly positive. Soil texture and C content were identified as the most important factors associated with priming effects, with sandy soils from tropical and mid‐latitudes supporting the highest soil priming effect intensity, and soils with greater C content and fine textures from high latitudes maintaining the lowest soil priming effects. The negative association between C content and soil priming effect intensity was also indirectly driven by changing mean annual temperature, net primary productivity, and fungi : bacteria ratio. Using this information, we generated a global map of soil priming effect intensity, and found that the priming was lower at high latitudes and higher at lower latitudes. Main conclusions Global patterns of soil priming effect intensity can be predicted using environmental data, with soil texture and C content playing a predominant role in explaining in priming effects. These effects were also indirectly driven by climate, vegetation and soil microbial properties. We present the first global atlas of soil priming effect intensity and advance our knowledge on the potential mechanisms underlying soil priming effect intensity, which are integral to improving the climate change and soil C dynamics components of Earth System models.

Vocalization of Bryde's whales ( Balaenoptera edeni ) in the Beibu Gulf, China - Zhi‐Tao Wang; Peng‐Xiang Duan; Mo Chen; Zhi‐Gang Mei; Xiao‐Dong Sun; Zhi‐Wen Nong; Mei‐Han Liu; Tomonari Akamatsu; Ke‐Xiong Wang; Ding Wang (Marine Mammal Science, 2022)
The presence of Bryde's whales ( Balaenoptera edeni ) in the Beibu Gulf, China has been reported since 2016. In the current study, in situ Bryde's whale vocalizations were recorded. Bouts of frequency modulated repetitive and diversified calls were recorded. Repetitive calls were recorded when 1–3 whales were present within 2 km of the boat and were probably emitted by a single whale and functioned as contact calls. Repetitive calls were divided into biphonation downswept tonals and downswept tonals. Diversified calls were recorded when 4–7 whales were present within 2 km of the boat and were probably associated with acoustic exchanges between or among conspecifics. Diversified calls occasionally contained inflection points, frequency jumps, and break point features. The frequency band of Bryde's whale vocalizations overlapped highly with background noise. Most vocalizations in the current study were different than those previously reported for this species. Therefore, the findings of this study provide more information on the known acoustic repertoire of Bryde's whales and provide a basis for noninvasive monitoring of Bryde's whale with passive acoustic methods and for developing mitigation and conservation protocols to ensure their future viability.

Exogenous ABA promotes aroma biosynthesis of postharvest kiwifruit after low-temperature storage - Xueyuan Han; Xiaoyu Wang; Chi Shen; Yiwei Mo; Rungang Tian; Linchun Mao; Zisheng Luo; Huanyi Yang (Planta, 2022)

miR-183-5p promotes proliferation, invasion, and glycolysis of thyroid carcinoma cells by targeting FOXO1 - Chun Han; Kangnan Mo; Lin Jiang; Kejing Wang; Lisong Teng (Molecular and Cellular Biochemistry, 2022)

Neural responses to facial attractiveness in the judgments of moral goodness and moral beauty - Qiuping Cheng; Zhili Han; Shun Liu; Yilong Kong; Xuchu Weng; Lei Mo (Brain Structure and Function, 2022)

Geochemistry and Sr–Nd isotopes of the Late Mesozoic lamprophyres in the Chaohu area, eastern China : Petrogenesis and tectonic implications - Mo Chen; Longming Li; Tianxiang Kan; Hang Liu; Xilin Zhao; Jiahao Li; Xu Han (Island Arc, 2022)
Late Mesozoic lamprophyres are widespread in the Chaohu area of the Lower Yangtze region, eastern China. These mantle‐derived rocks are of great significance for understanding the characteristics of mantle source and tectonic environment of eastern China during the Late Mesozoic. The lamprophyres from the Chaohu area can be divided into two types. The type‐I lamprophyres have low SiO 2 (43.8–44.5 wt.%) and TiO 2 (1.06–1.14 wt.%), high MgO (13.5–17.5 wt.%) and high contents of compatible elements, and are enriched in LREE and LILE but depleted in HFSE. They have high initial 87 Sr/ 86 Sr (0.70767–0.70904) and negative εNd ( t ) (−4.8 to −4.4). The type‐II lamprophyres are characterized by low contents of SiO 2 (43.0–45.4 wt.%), high TiO 2 (1.74–2.55 wt.%), MgO (9.17–15.4 wt.%), and compatible elements. They are also enriched in LREE and LILE but depleted in HFSE. They show enriched Sr‐Nd isotopic compositions with initial 87 Sr/ 86 Sr values (0.70773–0.70886) and εNd ( t ) values (−8.6 to −7.8). The type‐I lamprophyres show higher Mg # and MgO contents but significant lower TiO 2 than the type‐II lamprophyres. In addition, the type‐I lamprophyres have relatively similar initial 87 Sr/ 86 Sr ratios but higher εNd( t ) values than the type‐II lamprophyres. The difference of geochemical characteristics between the type‐I and type‐II lamprophyres may be caused by different degrees of partial melting of an amphibole‐bearing garnet lherzolite mantle. The lithospheric mantle was metasomatised by the fluids caused by the rollback of the Paleo‐Pacific plate subduction during the Late Cretaceous.

Community structure of environmental microorganisms associated with COVID-19 affected patients - Weihua Zhang; Guoxin Mo; Jie Yang; Xingshuo Hu; Hujie Huang; Jing Zhu; Pei Zhang; Han Xia; Lixin Xie (Aerobiologia, 2021)
To clarify the characteristics and distribution of hospital environmental microbiome associated with confirmed COVID-19 patients. Environmental samples with varying degrees of contamination which were associated with confirmed COVID-19 patients were collected, including 13 aerosol samples collected near eight patients in different wards, five swabs from one patient’s skin and his personal belongings, and two swabs from the surface of positive pressure respiratory protective hood and the face shield from a physician who had close contact with one patient. Metagenomic next-generation sequencing (mNGS) was used to analyze the composition of the microbiome. One of the aerosol samples (near patient 4) was detected positive for COVID-19, and others were all negative. The environmental samples collected in different wards possessed protean compositions and community structures, the dominant genera including Pseudomonas , Corynebacterium , Neisseria , Staphylococcus , Acinetobacter , and Cutibacterium . Top 10 of genera accounted for more than 76.72%. Genera abundance and proportion of human microbes and pathogens radiated outward from the patient, while the percentage of environmental microbes increased. The abundance of the pathogenic microorganism of medical supplies is significantly higher than other surface samples. The microbial compositions of the aerosol collected samples nearby the patients were mostly similar to those from the surfaces of the patient's skin and personal belongings, but the abundance varied greatly. The positive rate of COVID-19 RNA detected from aerosol around patients in general wards was quite low. The ward environment was predominantly inhabited by species closely related to admitted patients. The spread of hospital microorganisms via aerosol was influenced by the patients’ activity.

Deep Learning Model for the Automated Detection and Histopathological Prediction of Meningioma - Hua Zhang; Jiajie Mo; Han Jiang; Zhuyun Li; Wenhan Hu; Chao Zhang; Yao Wang; Xiu Wang; Chang Liu; Baotian Zhao; Jianguo Zhang; Kai Zhang (Neuroinformatics, 2021)

Proteome landscape and spatial map of mouse primordial germ cells - Pan Wang; Yilong Miao; Xiao-Han Li; Na Zhang; Qilong Wang; Wei Yue; Shao-Chen Sun; Bo Xiong; Jie Qiao; Mo Li (Science China Life Sciences, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Generation of Hepatic Progenitor Cells from the Primary Hepatocytes of Nonhuman Primates Using Small Molecules - Da Hee Hong; Changhee Lee; Yohan Kim; Seung Bum Lee; Su-Cheol Han; Sung Joo Kim; Heung-Mo Yang; Dongho Choi; Jaemin Jeong; Kiyoung Ryu (Tissue Engineering and Regenerative Medicine, 2021)

Evaluation of Polycyclic Aromatic Hydrocarbons (PAHs) in Bamboo Shoots from Soil - Danyu Shen; Xinyue Yuan; Yongxiang Han; Runhong Mo; Donglian Zhong; Fubin Tang; Yihua Liu (Bulletin of Environmental Contamination and Toxicology, 2021)

A novel apoptosis probe, cyclic ApoPep-1, for in vivo imaging with multimodal applications in chronic inflammatory arthritis - In-Seop So; Jin Hee Kang; Jung Wan Hong; Shijin Sung; Al Faruque Hasan; Keum Hee Sa; Seung Woo Han; In San Kim; Young Mo Kang (Apoptosis, 2021)

Fracture characterization in oil-based mud boreholes using image logs: example form tight sandstones of Lower Cretaceous Bashijiqike Formation of KS5 well area, Kuqa Depression, Tarim Basin, China - Rui Yuan; Denglin Han; Yangang Tang; Hongxing Wei; Tao Mo; Chenchen Wang (Arabian Journal of Geosciences, 2021)

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

Integrated bioinformatics analyses identified SCL3-induced regulatory network in Arabidopsis thaliana roots - Chun-Yue Weng; Mo-Han Zhu; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2020)

Acute and 13-week subchronic toxicity studies of hot-water extract of Cynanchi wilfordii Radix in Sprague-Dawley rats - Chung-Tack Han; Du-Yeol Kim; Chunja Nam; Seol-Hee Moon; Sun-Hee Park; Kyoung-Goo Han; Hye-Yeong Lee; Heung-Mo Bae; Cheol-Beom Park; Jai-Hyun So; Sukmo Kang; Jong-Koo Kang (Toxicological Research, 2020)

Influence of the degree of donor bone marrow hyperplasia on patient clinical outcomes after allogeneic hematopoietic stem cell transplantation - Feifei Tang; Xiaodong Mo; Xiaohui Zhang; Yu Wang; Chenhua Yan; Yuhong Chen; Huan Chen; Wei Han; Yao Chen; Fengrong Wang; Jingzhi Wang; Yuqian Sun; et al. (Science China Life Sciences, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Fine root dynamics responses to nitrogen addition depend on root order, soil layer, and experimental duration in a subtropical forest - Wenjuan Wang; Qifeng Mo; Xiaoge Han; Dafeng Hui; Weijun Shen (Biology and Fertility of Soils, 2019)

Correction to: Effects of AMPK on Apoptosis and Energy Metabolism of Gastric Smooth Muscle Cells in Rats with Diabetic Gastroparesis - Mo-han Zhang; Xue-sen Fang; Jun-yu Guo; Zheng Jin (Cell Biochemistry and Biophysics, 2019)

Experimental Study on the Effect of Cation Exchange Capacity on Slurry Properties - Pinghe Sun; Binkui Zhao; Han Cao; Jingyuan Wang; Dingqiang Mo; Shaohe Zhang (Geotechnical and Geological Engineering, 2019)

Effects of AMPK on Apoptosis and Energy Metabolism of Gastric Smooth Muscle Cells in Rats with Diabetic Gastroparesis - Mo-han Zhang; Xue-sen Fang; Jun-yu Guo; Zheng Jin (Cell Biochemistry and Biophysics, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Synthesis and biological evaluation of novel SIPI-7623 derivatives as farnesoid X receptor (FXR) antagonists - Si-Yun Nian; Guo-Ping Wang; Zheng-Li Jiang; Ying Xiao; Mo-Han Huang; Yi-Huan Zhou; Xiang-Duan Tan (Molecular Diversity, 2019)

Effects of insulin-like growth factor-1 on endoplasmic reticulum stress and autophagy in rat gastric smooth muscle cells cultured at different glucose concentrations in vitro - Xue-sen Fang; Mo-han Zhang; Jun-yu Guo; Zheng Jin (Molecular and Cellular Biochemistry, 2019)

MicroRNA 429 regulates the expression of CHMP5 in the inflammatory colitis and colorectal cancer cells - Ji-Su Mo; Seol-Hee Han; Ki-Jung Yun; Soo-Cheon Chae (Inflammation Research, 2018)

Uptake effects of toxic heavy metals from growth soils into jujube and persimmon of China - Yuewen Zheng; Danyu Shen; Shutian Wu; Yongxiang Han; Shiliang Li; Fubin Tang; Zhanglin Ni; Runhong Mo; Yihua Liu (Environmental Science and Pollution Research, 2018)

Distribution, relationship, and risk assessment of toxic heavy metals in walnuts and growth soil - Yongxiang Han; Zhanglin Ni; Shiliang Li; Minghua Qu; Fubin Tang; Runhong Mo; Caifen Ye; Yihua Liu (Environmental Science and Pollution Research, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Complete genome of Cobetia marina JCM 21022T and phylogenomic analysis of the family Halomonadaceae - Xianghai Tang; Kuipeng Xu; Xiaojuan Han; Zhaolan Mo; Yunxiang Mao (Journal of Oceanology and Limnology, 2018)

Gene mutations and clinical phenotypes in 15 Chinese children with cryopyrin-associated periodic syndrome (CAPS) - Caifeng Li; Xiaohua Tan; Junmei Zhang; Shipeng Li; Wenxiu Mo; Tongxin Han; Weiying Kuang; Yifang Zhou; Jianghong Deng (Science China Life Sciences, 2017)

A nationwide study of the incidence rate of herb-induced liver injury in Korea - Jung-Hyo Cho; Dal-Seok Oh; Sang-Hoon Hong; Heung Ko; Nam-Hun Lee; Sang-Eun Park; Chang-Woo Han; Seung-Mo Kim; Young-Chul Kim; Kang-San Kim; Chang-Won Choi; Seon-My Shin; et al. (Archives of Toxicology, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Analysis of diagnosis and treatment of lipoblastomatosis - Zhiqiang Mo; Xianghui Xie; Huanmin Wang; Hong Qin; Wei Han; Xiaosong Li (Science China Life Sciences, 2017)

In vitro propagation of the endangered tree fern Cibotium barometz through formation of green globular bodies - Rongpei Yu; Guangfei Zhang; Han Li; Hua Cao; Xijun Mo; Min Gui; Xuhong Zhou; Yalian Jiang; Shenchong Li; Jihua Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Autoimmunity and dysmetabolism of human acquired immunodeficiency syndrome - Yan-Mei Huang; Xue-Zhi Hong; Jia-Hua Xu; Jiang-Xi Luo; Han-You Mo; Hai-Lu Zhao (Immunologic Research, 2016)

Mechanism and Regulation of Autophagy and Its Role in Neuronal Diseases - Zhiping Hu; Binbin Yang; Xiaoye Mo; Han Xiao (Molecular Neurobiology, 2015)

Erratum to: Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Expressed sequence tag analysis and annotation of genetic information from the freshwater clam, Pisidium (Neopisidium) coreanum endemic to Korea - Ji Eun Jeong; Se Won Kang; Hee-Ju Hwang; So Young Park; Bharat Bhusan Patnaik; Changmu Kim; Soonok Kim; Myung-Mo Nam; Jae Bong Lee; Tae Hun Wang; Eun Bi Park; Sun Shin Yi; et al. (Genes & Genomics, 2015)

Characterization of Physa acuta expressed sequence tags and transcript mining following cadmium exposure - Ji Eun Jeong; Bharat Bhusan Patnaik; Se Won Kang; Hee-Ju Hwang; So Young Park; Tae Hun Wang; Eun Bi Park; Jae Bong Lee; Myung-Mo Nam; Yong Hun Jo; Yeon Soo Han; Jun-Sang Lee; et al. (Genes & Genomics, 2015)

Cucurbitacin D induces cell cycle arrest and apoptosis by inhibiting STAT3 and NF-κB signaling in doxorubicin-resistant human breast carcinoma (MCF7/ADR) cells - Jin Mo Ku; Soon Re Kim; Se Hyang Hong; Han-Seok Choi; Hye Sook Seo; Yong Cheol Shin; Seong-Gyu Ko (Molecular and Cellular Biochemistry, 2015)

Effect of the Shenfu Injection Combined with Early Goal-Directed Therapy on Organ Functions and Outcomes of Septic Shock Patients - Mao-qin Li; Cui-gai Pan; Xiao-meng Wang; Xun Mo; Zai-xiang Shi; Ji-yuan Xu; Yan-jun Xu; Guan-jie Han (Cell Biochemistry and Biophysics, 2015)

Evaluation of 1-G Similitude Law in Predicting Behavior of a Pile-Soil Model - Jung-In Choi; Min-Taek Yoo; Eui-Kyu Yang; Jin-Tae Han; Myoung-Mo Kim (Marine Georesources & Geotechnology, 2015)

New record of the short-tailed pipefish, Microphis brachyurus brachyurus (Teleostei: Syngnathidae), with a key to the species of the family Syngnathidae from Korea - Sang-Yun Han; Jun Mo Lee; Jin-Koo Kim (Ocean Science Journal, 2014)

Parallel simulation of groundwater flow in the North China Plain - Tangpei Cheng; Jingli Shao; Yali Cui; Zeyao Mo; Zhong Han; Ling Li (Journal of Earth Science, 2014)

Ranging behavior of eastern hoolock gibbon (Hoolock leuconedys) in a northern montane forest in Gaoligongshan, Yunnan, China - Dao Zhang; Han-Lan Fei; Sheng-Dong Yuan; Wen-Mo Sun; Qing-Yong Ni; Liang-Wei Cui; Peng-Fei Fan (Primates, 2014)

Survey of encoding and decoding of visual stimulus via FMRI: an image analysis perspective - Mo Chen; Junwei Han; Xintao Hu; Xi Jiang; Lei Guo; Tianming Liu (Brain Imaging and Behavior, 2014)

Impact of matrix metalloproteinase-8 gene variations on the risk of thoracic aortic dissection in a Chinese Han population - Xiao-Zeng Wang; Xiao-Mo Du; Quan-Min Jing; Xing-Xing Li; Ruo-Xi Gu; Jiao Wang; Ya-Ling Han (Molecular Biology Reports, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Fertilizer N uptake of paddy rice in two soils with different fertility under experimental warming with elevated CO2 - Hong-Shik Nam; Jin-Hyeob Kwak; Sang-Sun Lim; Woo-Jung Choi; Sun-Il Lee; Dong-Suk Lee; Kwang-Seung Lee; Han-Yong Kim; Sang-Mo Lee; Miwa Matsushima (Plant and Soil, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Association of interleukin-1 receptor-associated kinase (IRAK1) gene polymorphisms (rs3027898, rs1059702) with systemic lupus erythematosus in a Chinese Han population - Yu Zhai; Ke Xu; Rui-Xue Leng; Han Cen; Wei Wang; Yan Zhu; Mo Zhou; Chen-Chen Feng; Dong-Qing Ye (Inflammation Research, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Association of AFF1 rs340630 and AFF3 rs10865035 polymorphisms with systemic lupus erythematosus in a Chinese population - Han Cen; Rui-Xue Leng; Wei Wang; Mo Zhou; Chen-Chen Feng; Gui-Mei Chen; Rui Li; Hai-Feng Pan; Xiang-Pei Li; Dong-Qing Ye (Immunogenetics, 2012)

3D Numerical Simulation of a Soil-Pile System Under Dynamic Loading - Seong-Hwan Kim; Sun-Yong Kwon; Myoung-Mo Kim; Jin-Tae Han (Marine Georesources & Geotechnology, 2012)

Environmental assessment of sewage effluent disinfection system: electron beam, ultraviolet, and ozone using life cycle assessment - Kun-Mo Lee; Seungho Yu; Yo-Han Choi; Myunjoo Lee (The International Journal of Life Cycle Assessment, 2012)

Activation of a flavin monooxygenase gene YUCCA7 enhances drought resistance in Arabidopsis - Minyoung Lee; Jae-Hoon Jung; Doo-Yeol Han; Pil Joon Seo; Woong June Park; Chung-Mo Park (Planta, 2012)

Re-expression of miR-21 contributes to migration and invasion by inducing epithelial-mesenchymal transition consistent with cancer stem cell characteristics in MCF-7 cells - Mingli Han; Manran Liu; Yimeng Wang; Zhiqiang Mo; Xiaokai Bi; Zhirong Liu; Yuanming Fan; Xin Chen; Chengyi Wu (Molecular and Cellular Biochemistry, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

5-Phenylselenyl- and 5-methylselenyl-methyl-2′-deoxyuridine induce oxidative stress, DNA damage, and caspase-2-dependent apoptosis in cancer cells - Byeong Mo Kim; Ambadas B. Rode; Eun Jong Han; In Seok Hong; Sung Hee Hong (Apoptosis, 2012)

Characterization of EmpA protease in Vibrio anguillarum M3 - Yifan Han; Zhaolan Mo; Peng Xiao; Bin Hao; Jie Li; Guanpin Yang (Journal of Ocean University of China, 2011)

Natural 15N abundance of paddy rice (Oryza sativa L.) grown with synthetic fertilizer, livestock manure compost, and hairy vetch - Soek-In Yun; Sang-Sun Lim; Gwang-Sung Lee; Sang-Mo Lee; Han-Yong Kim; Hee-Myong Ro; Woo-Jung Choi (Biology and Fertility of Soils, 2011)

Dry matter and nitrogen accumulation and partitioning in rice (Oryza sativa L.) exposed to experimental warming with elevated CO2 - Han-Yong Kim; Sang-Sun Lim; Jin-Hyeob Kwak; Dong-Suk Lee; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Plant and Soil, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Complete nucleotide sequence and genome organization of a Chinese isolate of Tobacco vein distorting virus - Xiao-han Mo; Zheng-bin Chen; Jian-ping Chen (Virus Genes, 2010)

Transmutation of ancient settlements and environmental changes between 6000–2000 aBP in the Chaohu Lake Basin, East China - Li Wu; Xinyuan Wang; Kunshu Zhou; Duowen Mo; Cheng Zhu; Chao Gao; Guangsheng Zhang; Lan Li; Li Liu; Weiguang Han (Journal of Geographical Sciences, 2010)

Oligometastases confined one organ from colorectal cancer treated by SBRT - Jin-Kyu Kang; Mi-Sook Kim; Jin Ho Kim; Seong Yul Yoo; Chul Koo Cho; Kwang Mo Yang; Hyung Jun Yoo; Young Seok Seo; Dong Han Lee; Hae Jin Kang; Young Han Kim; Ui-Sup Shin (Clinical & Experimental Metastasis, 2010)

1D crustal velocity structure beneath broadband seismic stations in the Okcheon Fold Belt of Korea by receiver function analysis - Sung Il Han; Jung Mo Lee; Tae-Seob Kang (Geosciences Journal, 2010)

Antibacterial activity of novel naphthoquiones derivatives - Yongseog Chung; Ren shu Quan; Hyeon Mo Chang; Soo Han Kwon; Soon-Ja Kim; Young-Sam Im; Kyeong Seob Shin; Kyung-Do Park; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2009)

Analysis of genetic diversity and population structure of rice cultivars from Korea, China and Japan using SSR markers - Weiguo Zhao; Jong-Wook Chung; Kyung-Ho Ma; Tae-San Kim; Seung-Min Kim; Dong-Il Shin; Chang-Ho Kim; Han-Mo Koo; Yong-Jin Park (Genes & Genomics, 2009)

Relating Tree Ring Chemistry of Pinus densiflora to Precipitation Acidity in an Industrial Area of South Korea - Jin-Hyeob Kwak; Sang-Sun Lim; Hyun-Jung Park; Sun-Il Lee; Kye-Han Lee; Han-Yong Kim; Scott X. Chang; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Water, Air, & Soil Pollution, 2009)

SLC11A1 Polymorphisms Are Associated with the Risk of Chronic Obstructive Pulmonary Disease in a Korean Population - Eun Jin Kim; Kyung Mee Kim; Sun Ha Park; Jong Sik Kim; Won Kee Lee; Sung Ick Cha; Chang Ho Kim; Young Mo Kang; Sung Beom Han; Tae Hoon Jung; Jae Yong Park (Biochemical Genetics, 2008)

Litterfall Dynamics of an Evergreen Broadleaf Forest and a Pine Forest in the Subtropical Region of China - Zhi An Li; Bi Zou; Han-ping Xia; Hai Ren; Jiang-ming Mo; Hong Weng (Forest Science, 2005)
Monthly litterfall was monitored over a 10-year period from an evergreen broadleaf forest (EBF) and a pine forest (PF) in subtropical South China. During this period, litter was also collected bimonthly from the forest floor for 2 years. Total annual litterfall in EBF fluctuated around 9 Mg ha−1 with leaves, branches, and miscellanea accounting for 52.5%, 22.2%, and 25.3%, respectively. Total annual litterfall alternated between high and low values in consecutive years. Storms and pest outbreaks were responsible for most of the peaks in both monthly and annual litterfall. Litter from each of 43 species was recorded, but 9 species contributed about 85% of total litterfall. Dominant species shed their leaves in a more regular pattern with peaks mainly from Jan. to Mar. Pine forest (Pinus massoniana) produced much less litterfall than EBF, with a mean of 2.7 Mg ha−1. Here, leaves accounted for 73.2% of total litterfall, branches only 11.4%, and miscellanea 15.4%. Litter on the ground amounted to 5.2 Mg ha−1 in EBF and 2.9 Mg ha−1 in PF. The results show that this climax forest has much higher litterfall and forest floor mass than the pine forest, and litterfall is rather stable with regard to annual variation. FOR. SCI. 51(6):608–615.

Thermostable Alkaline Protease from a Novel Marine Haloalkalophilic Bacillus Clausii Isolate - C. Ganesh Kumar; Han-Seung Joo; Yoon-Mo Koo; Seung R. Paik; Chung-Soon Chang (World Journal of Microbiology and Biotechnology, 2004)

Antigenicity of the region encoded by exon8 of the human serine protease, HtrA2/Omi, is associated with its protein solubility - Hyo-Jin Park; Ju-Youn Choi; Young-Mo Seong; Chul Han; Sung-Joo Kim Yoon; Seongman Kang; Hyangshuk Rhim (Biotechnology Letters, 2003)

Pathogenicity and vaccine efficacy of a thymidine kinase gene deleted infectious laryngotracheitis virus expressing the green fluorescent protein gene - M. G. Han; C. H. Kweon; I. P. Mo; S. J. Kim (Archives of Virology, 2002)

Evaluation of nitrate contamination sources of unconfined groundwater in the North Han River basin of Korea using nitrogen isotope ratios - Woo-Jung Choi; Gwang-Hyun Han; Hee-Myong Ro; Sun-Ho Yoo; Sang-Mo Lee (Geosciences Journal, 2002)